Origin, conception and treatment of the tourist destination life cycle: a refletion on the Butler model (Revista Científica Compendium, 2018)
Since its inception, the Tourist Destination Life Cycle Model (TDLCM), developed in 1980 by Richard Butler, led to great discussions and generated a vast literature focused on its application. The scrutiny, of which it has been object, has been extensive and its adaptations have been wide. In this work, through a bibliographical review, it is sought to establish the origin, conception and treatment, which has carried over more than three decades, in order to determine its validity as a strategic management and planning model within the field of tourism and its conceptual limitations.
Keywords: Life cycle; origin; conception and treatment